Language learning strategies instruction via English for community-based tourism blended lessons to enhance speaking ability of Thai EFL youth guides - Malinee Phaiboonnugulkij (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study aims to investigate the English-speaking ability of the high and low-proficiency youth guides after studying English for Community-based Tourism at Khokkrachai blended lessons and examine their use of total and individual learning strategies in these blended lessons. The sample group consists of 32 youth guides who were secondary students from Nakhon Ratchasima, Thailand. They were selected by using a cluster random sampling technique. The instruments included an English for Community-based Tourism Youth Guides blended lesson, a speaking test and the rating scale, a language learning strategies questionnaire and a coding scheme. Means, standard deviations, paired-samples t-test and content analysis were used in data analysis. Results from the study showed that the performance of the high- and low-proficiency youth guides’ groups had a significant difference between pre- and post-tests in both the total and six speaking aspect scores at the .00 level. The scores of both groups significantly improved. The results also indicated that the youth guides always used their learning strategies to learn during the three blended lessons. The high-proficiency youth guides utilised each language learning strategy in more meaningful, systematic, sophisticated and holistic ways than the low-proficiency youth guides. These results yielded insightful and substantive data about the instruction of language learning strategies in English within a specific field, English for community-based tourism with blended learning in Thailand.